Single and Multi-Soliton Solutions for a Spectrally Deformed Set of Maxwell-Bloch Equations - BARAN, MEHMET KADİR (MDPI, 2019)
A specific spectral deformation of the Maxwell-Bloch equations of nonlinear optics is investigated. The Darboux transformation formalism is adapted to this spectrally deformed system to construct its single and multi-soliton solutions. The Effects of spectral deformation on soliton behaviour is studied.
Keywords: maxwell-bloch equations; solitons; spectral deformation; darboux transformations; lax pair; zero curvature representation; soliton collision; OPTICAL SOLITONS